DNA damage and nonhomologous end joining in excitotoxicity: neuroprotective role of DNA-PKcs in kainic acid-induced seizures. - Neema, M; Navarro-Quiroga, I; Chechlacz, M; Gilliams-Francis, K; Liu, J; Lamonica, K; Lin, S; Naegele, JR (2005)
DNA repair plays a critical, but imprecisely defined role in excitotoxic injury and neuronal survival throughout adulthood. We utilized an excitotoxic injury model to compare the location and phenotype of degenerating neurons in mice (strain 129-C57BL) deficient in the catalytic subunit of the DNA-dependent protein kinase (DNA-PKcs), an enzyme required for nonhomologous end joining (NHEJ). Brains from untreated adult heterozygous and DNA-PKcs null mice displayed comparable cytoarchitecture and undetectable levels of cell death. By day 1, and extending through 4 days following kainic acid-induced seizures, brains from DNA-PKcs null mice showed widespread neurodegeneration that encompassed the entire hippocampal CA1-CA3 pyramidal cell layer, entorhinal cortex, and lateral septum, with relative sparing of the dentate gyrus granule cell layer and hilus, as judged by toluidine blue, Fluoro-Jade B, and terminal dUTP nick end labeling staining. In contrast, seizure-related neurodegeneration in heterozygous littermates was limited to the CA3 region of the hippocampus. NeuN and calbindin staining revealed a selective decrease in the number and density of NeuN-positive neurons in the pyramidal layers of degenerating regions in both heterozygous and DNA-PKcs null mice. To elucidate the mechanisms leading to cell death, we examined an involvement of the p53 pathway, known to be induced by DNA damage. Addition of pifithrin-alpha, a p53 inhibitor, or expression of a dominant-negative p53 rescued neurons from kainate-induced excitotoxic cell death in primary cortical cultures derived from wildtype, DNA-PKcs heterozygous, or DNA-PKcs null neonatal mice. Moreover, pifithrin-alpha prevented kainate-induced loss of mitochondrial membrane potential, dendrite degeneration, and cell death. Results suggest that NHEJ plays a neuroprotective role in excitotoxicity, within the perforant, Schaffer collateral, hippocampal-septal, and temperoammonic pathways, in part by repairing DNA damage that would otherwise result in activation of a p53-dependent apoptotic cascade.